Reprodução: a subjetividade emergente numa narrativa distópica e pós-autônoma - Sommer, Vera Lucia (2017)
Technological changes which vertiginously took place at the end of the 20th century and the beginning of the 21st century had an impact on literary and artistic contemporary production and on social relations. Furthermore, they were incorporated into both the unconscious and the nature of the Western capitalist system. Genres, styles, categories and senses are outdated classifications because they cannot handle the art context of the 2000s. Photographs, audios, graphics, cinema, printed and virtual texts, plus several other materials and visual arts, they all dialogue to the point of mixing, transmuting and overflowing the frontiers and boundaries which prevail in modernity. Could one still speak of literature and of Arts? Those are two among the main questions brought into debate in this research about the literary narrative produced in Latin America in postmodern era. The research analyses the novel Reprodução (Literary work not translated into English) by the Brazilian writer and journalist Bernardo Carvalho. The ways the individuals make themselves visible “here and now”, whether on social networks or in the off-line world have also gone through mutations to the point of (re)bringing about other subjectivities. They are noteworthy ways of seeing, feeling, experiencing and looking at the surrounding world and having other approaches, perceptions, different sensibility, humanities and subjectivities. They are signs of modernity and indicia of postmodernity. Neither is the modern old, nor is the postmodern new. Here and there, inside and outside. Literature and post literature.